The Impact of Talking Stick Cooperative Learning on Students’ Geography Performance in Senior High School - Nova Yulizar; Syafri Anwar (Universitas Pendidikan Ganesha, 2025)
The loss of student interest in learning is caused by teachers are less effective in applying appropriate learning models for Geography learning activities. This problem also has an impact on low student learning outcomes. Based on this, this study aims to analyze the effect of the Talking Stick learning model on the geography learning outcomes of high school students in grade XII. This study uses a quantitative approach with a quasi-experimental design. The study population was 90 students, while the sample consisted of 30 students. The data collection method used a test. The research instrument was a multiple-choice test. The data analysis technique employed inferential statistics, which included normality tests, homogeneity tests, and t-tests, using the SPSS 20 application. The results showed that students in the experimental class, taught using the Talking Stick model, obtained better average posttest scores than those in the control class. The results of the t-test revealed a significant difference between the pre- and post-application of the Talking Stick learning model in Geography learning. It was concluded that the Talking Stick learning model had a positive effect on students' geography learning outcomes.